Intra-specific pelage color variation in a South American small rodent species - Sandoval Salinas, Maria Leonor (2016)
Intra-specific color variation is often underestimated by researchers, and among mammalian species, intra-specific differences in coloration are poorly documented for most species. The main goal of this study was to apply an objective color measurement methodology to the study of a specific problem: the detection, if any, of patterns of changes in the fur color of specimens of Akodon budini in relation to biological (i.e., sex) and environmental (i.e., season) variables. We hypothesize that male coat color will be more homogeneous than that of females and that the winter coat color will be darker than that of summer, the latter being orange. We measured the pelage color on five points over the dorsal surface of 26 A. budini museum specimens region using a spectroradiometer and a diffuse illumination cabin. We used Principal Component Analysis to describe the association between the color variables, sex and season, and each of the observations. We then used general linear models of Analysis of Variance to examine relationships between color data, season, and sex. The results clearly confirm the hypothesis related to seasonal coat color change but do not directly confirm the hypothesis related to changes in coat color in relation to sex, and we show the complexity of the studied pattern. In conclusion, undoubtedly, the studied variables should accordingly be taken into account when studying the coloration of specimens for characterization, identification and discrimination of different taxonomic units based on color.